Magnetic resonance imaging histogram analysis of corpus callosum in a functional neurological disorder - Baykara, Sema; Baykara, Murat; Mermi, Osman; Yildirim, Hanefi; Atmaca, Murad (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: The aim of the present study was to examine and compare the corpus callosum (CC) via histogram analysis (HA) on T1-weighted MR images of patients diagnosed with Functional Neurological Disorder (FND) and healthy controls. Materials and methods: The study group included 19 female patients diagnosed with FND, and the control group included 20 healthy subjects. All participants were scanned with a 1.5 T MR scanner. A high-resolution structural image of the entire brain was obtained with sagittal 3D spiral fast spin echo T1-weighted images. Gray level intensity, standard deviation of the histogram, entropy, uniformity, skewness, and kurtosis values were determined with texture analysis. A student's t-test was used to compare the group data. P < 0.05 was accepted as statistically significant. Results: It was determined that the mean gray level intensity, standard deviation of the histogram, entropy calculated by the maximum, median and variance and size M percentage values were higher in patients with FND. Kurtosis and size U percentages values were lower in patients with FND. Conclusion: In the present study, analysis of CC with T1-weighted MR image HA demonstrated significant differences between FND patients and healthy controls. The study findings indicated that HA is a beneficial technique for demonstrating textural variations between the CCs of patients with FND and healthy controls using MR images.
Keywords: Conversion disorder; somatoform disorders; corpus callosum; histogram; magnetic resonance imaging